8.PRE AND POST EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY (ESWL) URINE CULTURE AS A GUIDE FOR ANTIBIOTICS MANAGEMENT (Iraqi Journal of Medical Sciences, 2018)
Background:The lifetime prevalence of kidney stone disease is estimated at 1-15%. The positive urine cultures can be obtained not only from Struvite stones, but also from calcium oxalate stones and also high levels of endotoxins are found both in infection stones (Struvite and carbonate apatite stones), and in non-infection stones. High concentrations of endotoxins (lipopolysaccharides) are thought to be released in the systemic circulation during stone treatment, inducing a systemic inflammatory response (SIRS) and this leads to urosepsis. Pre-Extracorporeal shock wave lithotripsy (ESWL) prophylactic antibiotics have an important role in reducing post-SWL infections, however, previous studies reported conflicting results. The issue of administering prophylactic antibiotics remains controversial in patients with sterile urine undergoing ESWL.Objective: To evaluate possible risk factors for post ESWL bacteriuria and consequently to identify patients with higher danger for urinary tract infection (UTI) or sepsis.Methods: Urine samples from 50 patients underwent ESWL, were collected by clean catch mid-stream urine collection method in sterile containers. Those patients were attending and admitting to Al-Imamein Al-Kadhimein Medical City during the period from October 2016 to January 2017. All patients had a urine culture performed before and after shock wave lithotripsy. Statistical analysis was performed with Epi-Info 7 and Excel programs. Statistical significance was evaluated using the Fisher's exact test with p